Elämän pokeri. - Ruusumaa, Jukka, 1962-; Anttila, Vesa, (Vesa Antti Kalervo); Elo, Heikki, 1964-; Kosunen, Rele, 1962-2023; Kuorikoski, Pekka; Lehtonen, Harri, (rumpali); Lönnholm, Kim, 1961-; Mattila, Saku; Murtojärvi, Henri; Murtojärvi, Johan; Mynttinen, Timo; Naatula, Ilkka; et al. ([Turku] : Sata-Artistit, 2000)
11 kappaletta.
Ruusumaa, Jukka (lauluääni, yhtye). - Säestävät muusikot: Mika Toivanen (kosketinsoittimet, ohjelmointi), Ilkka Naatula (kosketinsoittimet), Anssi Nykänen, Harri Lehtonen, Johan Murtojärvi (rummut), Harri Rantanen, Timo Mynttinen, Henri Murtojärvi (basso), Jarmo Nikku, Vesa Anttila, Saku Mattila (kitarat), Jukka Perko (alttosaksofini), Heikki Pohto (sopraanosaksofoni). Taustalaulajat: Heikki Elo, Jukka Ruusumaa, Kim Lönholm, Rele Kosunen, Heikki Pohto, Pekka Kuorikoski, Mika Toivanen, Make Tommila.
Keywords: Ruusumaa, Jukka, -- 1962- -- albumit; iskelmät